Pemanfaatan Media Card Short Ayat dalam Meningkatkan Motivasi dan Hasil Pembelajaran Al-Qur’an di Mi Nurul Huda Kota Bengkulu - Ahmad Suradi (Publikasi Pendidikan, 2018)
This study aims to describe the use of Card Short media in improving learning motivation and improve student learning outcomes in learning Al-Qur'an in MI Nurul Huda Bengkulu City. This research is a Classroom Action Research, that is research done in class with emphasis on improvement or improvement of process and practical learning. Based on the results of classroom action research can be concluded: (1) After using learning media card sort achievement motivation learning Al-Qur'an students MI Nurul Huda Bengkulu City has shown improvement. This can be seen where in cycle I this category sufficient. Then proceed to cycle II and obtained good category results in accordance with what is expected. (2) The use of media card sort is very effective in improving learning achievement of Al-Qur'an of MI Nurul Huda student of Bengkulu City, this can be seen in cycle II and obtained result of learning result with average value 80,27 with percentage of mastery learning 100 % with very high category and is in accordance with what is expected.